PRODUKSI MINUMAN INSTAN ROSELA DENGAN PENGONTROLAN PENGAWET DAN KONDISI OPERASI - Rahman, Nanik Astuti; Hudha, Mohammad Istnaeny; Anggorowati, Dwi Ana (jurnal ATMOSPHERE, 2023)
Rosella, a plant previously known as a flower, is now one of the plants that is often used as an object of research. Apart from simplicia, rosella is produced as a drink that has health benefits. Rosella production includes tea, jelly candy, instant drinks, and syrup. Roselle syrup production is carried out using process engineering, namely temperature and heating time. The addition of sugar was also intended to see its effect on preserving the syrup. The sugar added is varied at 1; 1.25; and 1.5 kg. In the syrup-making process, citric acid is added to enhance the taste. In this research, the heating temperature was carried out at the boiling temperature, with the heating time varying between 10 minutes, 15 minutes, and 20 minutes. Heating is also carried out at a temperature of 85 °C with a heating time of 30, 40, and 50 minutes. Laboratory analysis of the product is vitamin C analysis. To test consumer acceptance of the product, a hedonic test is carried out, which includes tests on taste, color, and structure (viscosity). The results obtained by this research were a syrup product with the largest vitamin C content, namely 25,251 mg/100 g, at a heating variation of 85 °C with a heating time of 50 minutes. Optimal sugar addition at 1.25 kg